2020
DOI: 10.1177/0954406219898220
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulation of droplet condensation on a surface with wettability gradient

Abstract: In this paper, a free energy lattice Boltzmann model of vapor condensation on a surface with a wettability gradient is developed and numerically analyzed to understand the microscopic behaviors of self-propelled droplet condensation. The effect of wettability gradient on droplet self-motion and coalescence as well as vapor condensation is examined and investigated. The condensation rate is presented during the whole droplet condensation process to analyze the role of wettability gradient on droplet condensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Li et al [11][12][13][14][15][16] improved the pseudopotential force model, wall wettability model and adjustable surface tension model under large density ratio, combined with the MRT-LBM model of multi-relaxation, gas state equation, etc., and simulated and studied the multiphase ow boiling heat transfer and phase transition process. The simulation of droplet impact on stationary walls based on the lattice Boltzmann method has also been thoroughly studied, such as the study of droplets, walls, environment and other aspects [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [11][12][13][14][15][16] improved the pseudopotential force model, wall wettability model and adjustable surface tension model under large density ratio, combined with the MRT-LBM model of multi-relaxation, gas state equation, etc., and simulated and studied the multiphase ow boiling heat transfer and phase transition process. The simulation of droplet impact on stationary walls based on the lattice Boltzmann method has also been thoroughly studied, such as the study of droplets, walls, environment and other aspects [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…7,19,20 In our previous study, it was shown that the behavior of a nano-droplet on a graphene surface can be influenced by the application of both constant and oscillating external electric fields. 20 Shen et al 21 considered the effect of surface wettability gradients on the dynamics of droplets, and they demonstrated droplet movement along the substrate gradient direction due to the non-uniform surface tension on the perimeter of a droplet base, which applied a directional force on the droplet. In some other studies, it was reported that the variation of wetting properties at the liquid-solid interface can provide outward forces caused by the surface energy variation, which may lead to drops spreading, partial bouncing, or complete bouncing depending on the impact conditions and surface wettability.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the lattice Boltzmann (LB) method has been recently emerged as a powerful method to study the fluid flow, 10,11 fluid-structure interaction, 12,13 and phase change problem. 14 In particular, the pseudo-potential multiphase LB model, that is, the Shan–Chen model imposes a short-range attraction between different phases to arise the phase segregation, thus directly capturing the phase interface in the absence of interface-tracking algorithms. 15 Besides, the nucleation sites in LB are activated by the natural evolution of the energy equation, which avoids the artificial assignment of the initial bubble nucleus.…”
Section: Introductionmentioning
confidence: 99%